ANALISIS PERMASALAHAN PEMBELAJARAN BIOLOGI BERDASARKAN KEAKTIFAN SISWA, KETERSEDIAAN FASILITAS, DAN VARIASI METODE PEMBELAJARAN DI MAS AL-WASHLIYAH 49 PASAR LEMBU - Amira Nasution, Aisyah; Shopia Isyfi, Aprillia; Aini, Nurul; Jumiati Hasibuan, Rizki; Arwita, Widya; Mukra, Rizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the problems in biology learning based on student activeness, availability of learning facilities, and variation of teaching methods at MAS Al-Washliyah 49 Pasar Lembu. This research employed a qualitative approach with a descriptive design. The research subject was a biology teacher of class X MIPA selected purposively. Data were collected through an online interview conducted via Zoom Meeting on March 12, 2026, using an interview guideline consisting of 30 questions. The data were analyzed using descriptive qualitative techniques through data reduction, data display, and conclusion drawing. The results showed that student activeness in learning was not evenly distributed, indicated by the presence of both active and passive students. Learning facilities were available; however, their utilization was not optimal due to limited quantity and access. In addition, the variation of teaching methods was still dominated by the lecture method, although innovative models such as Problem Based Learning (PBL) and Project Based Learning (PjBL) had been applied. These problems impacted students’ conceptual understanding and learning motivation. Therefore, improvements are needed through optimizing learning facilities and implementing more varied and innovative teaching methods.